Seychelles : Assessment of the Supervision and Regulation of the Financial Sector-Review of Financial Sector Regulation and Supervision. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews of Sector Regulation and Supervision for Seychelles. Regulation and supervision of the banking sector and foreign exchange bureaus in Seychelles is carried out by the Bank Supervision Division of the Central Bank. Supervision of the credit union and the insurance companies is less formal, and carried out within the Ministry of Finance. Supervision of the housing finance company is shared by the Ministry of Finance and the Ministry of Land Use and Habitat. The development bank has no designated supervisor, but its Board includes representatives from several key ministries.